Effects of dopamine donor pretreatment on graft survival after kidney transplantation: a randomized trial - Schnülle, Peter; Schmitt, Wilhelm; Weiß, Christel; Zeier, Martin; Drüschler, Felix (Clinical journal of the American Society of Nephrology, 2017)
Background and objectives: Donor dopamine improves initial graft function after kidney transplantation due to antioxidant properties. We investigated if a 4 µg/kg per minute continuous dopamine infusion administered after brain-death confirmation affects long-term graft survival and examined the exposure-response relationship with treatment duration. Design, setting, participants, & measurements: Five-year follow-up of 487 renal transplant patients from 60 European centers who had participated in the randomized, multicenter trial of dopamine donor pretreatment between 2004 and 2007 (ClinicalTrials.gov identifier: NCT00115115). Results: Follow-up was complete in 99.2%. Graft survival was 72.6% versus 68.7% (P=0.34), and 83.3% versus 80.4% (P=0.42) after death-censoring in treatment and control arms according to trial assignment. Although infusion times varied substantially in the treatment arm (range 0-32.2 hours), duration of the dopamine infusion and all-cause graft failure exhibited an exposure-response relationship (hazard ratio, 0.96; 95% confidence interval [95% CI], 0.92 to 1.00, per hour). Cumulative frequency curves of graft survival and exposure time of the dopamine infusion indicated a maximum response rate at 7.10 hours (95% CI, 6.99 to 7.21), which almost coincided with the optimum infusion time for improvement of early graft function (7.05 hours; 95% CI, 6.92 to 7.18). Taking infusion time of 7.1 hours as threshold in subsequent graft survival analyses indicated a relevant benefit: Overall, 81.5% versus 68.5%; P=0.03; and 90.3% versus 80.2%; P=0.04 after death-censoring. Conclusions: We failed to show a significant graft survival advantage on intention-to-treat. Dopamine infusion time was very short in a considerable number of donors assigned to treatment. Our finding of a significant, nonlinear exposure-response relationship disclosed a threshold value of the dopamine infusion time that may improve long-term kidney graft survival.